EFEKTIFITAS KINERJA PENGAWAS SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU KELAS IV UPT SPF SD INPRES BALANG BODDONG KECAMATAN TAMALATE KOTA MAKASSAR - Irmawati . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This study aims to find out: (1) How is the effectiveness of the performance of school supervisors at UPT SPF SD Inpres Balang Boddong, Tamalate District, Makassar City; (2) How is the Professional Competence of Class IV Teachers upt SPF SD Inpres Balang Boddong, Tamalate District, Makassar City and (3) How is the Effectiveness of The Performance of School Supervisors in Improving the Professional Competence of Class IV Teachers UPT SPF SD Inpres Balang Boddong, Tamalate District, Makassar City. This research is qualitative research using a descriptive approach. The subjects of this study were the superintendent of schools, the principal and the Class Teacher. Data collection techniques use interviews, observations and documentation. Data analysis techniques include data reduction, data presentation and conclusion drawing/verification The results of the study (1) The performance of the school superintendent at SD Inpres Balang Boddong in carrying out supervision is quite good, but it is still not optimal, especially in supervision activities. In addition, coaching activities are only at the time of the supervision; (2) The professional competence of teacher IV at SD Inpres Balang Boddong is quite good in teaching and learning activities where teachers compile lesson plans, master lesson materials, use learning media, build interaction with students, carry out assessment activities; and (3) The effectiveness of the performance of school supervisors in improving the professional competence of class IV teachers at SD Inpres Balang Boddong is still not optimal. This is because the school superintendent no longer follows up on his findings when conducting supervision so that the coaching carried out does not continue Keywords : Supervisory Performance, Competence, Teacher Professionalism